Socialisation and recruitment in Islamist movements: a comparison between the Muslim brotherhood and Al-Qaeda - Sivamurugan Pandian; Omar Gomaa Ahmed Mohamed; Nur Hafeeza Ahmad Pazil (Penerbit Universiti Kebangsaan Malaysia, 2020)
To date, a little work has been undertaken to compare the socialisation process between the Muslim Brotherhood and Al-Qaeda. According to critics, both are considered intermediate and extremist movements. While the Muslim Brotherhood utilises various methods of socialisation, Al-Qaeda utilises internet networks to recruit new members without looking at their prior history, leaving the Al-Qaeda movement extremely vulnerable. This article explores the main differences in the roles and impacts of the political movements the Muslim Brotherhood and Al-Qaeda. It focuses on the most significant aspect of the socialisation process on shaping alfard al-muslim the individual Muslim.